PENGEMBANGAN MEDIA BUKU TEMPEL UNTUK MENINGKATKAN KETRAMPILAN MENULIS TEGAK BERSAMBUNG SISWA KELAS III SD KRISTEN LENTERA AMBARAWA - Hendy Ardha Adventama, Redemptus; Dewi Koeswanti, Henny; Sefriani Sabuna, Erna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to assist in the development of learning media. Of course, the learning media used by educators in elementary schools. The media used is in the form of a scrapbook which is a book containing notes, pictures and colors that are used as reminders. Using scrapbooks can help educators convey learning material. Educators who experience changes from conventional teaching models change with the times. The scrapbook media used in this development research focuses on students' ability to write cursively. Cursive writing is writing that is written without lifting the writing utensil and is written continuously or not in separate sections. The ability to write upright in cursive also goes through several stages, so that students can learn with the process and assistance from scrapbook learning media.